Kinerja Keuangan dengan pendekatan Economic Value Added (EVA) pada PT. Mayora Indah, Tbk - Fira Febrina; Destian Arshad Darulmalshah Tamara; Mochamad Edman Syarief (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The research about financial performance using Economic Value Added (EVA) approach in PT. Mayora Indah, Tbk. for the year 2013-2020. EVA is one of method financial performance more accurate because account cost of capital. This research using method descriptive quantitative with a secunder data from balance sheet, income statement and dividend distribution audited PT. Mayora Indah, Tbk. for the year 2013-2020 and obtained from the page annual report of website PT. Mayora Indah, Tbk and website IDX. The result of this research is Economic Value Added of PT. Mayora Indah, Tbk. for the year 2014-2020 has a positive value. Although the value of EVA not showing increase every year but a positive value of EVA shows the company able to giving value added to stakeholder. In the 2013, the company has a negative value. It shows the company can’t to giving value added to investors. EVA negative value caused the NOPAT value smaller than capital charges.